CT-guided biopsy of subdiaphragmatic small renal nodule with the coaxial technique using MPR images - Saba, Luca; Saba, Francesco; Fellini, Federica (Acta Biomedica Atenei Parmensis, 2019)
Summary. Purpose: To demonstrate the advantages of CT-guided biopsy of subdiaphragmatic small renal nodule with the coaxial technique using MPR images. Methods: The study included retrospectively 12 patients who underwent CT-guided biopsy with 18 G needle of subdiaphragmatic small renal nodule (